Synthetic approach for the control of self-doping in luminescent organic semiconductors. (15th July 2022) - Kuimov, Anatoly D.; Becker, Christina S.; Shumilov, Nikita A.; Koskin, Igor P.; Sonina, Alina A.; Komarov, Vladislav Yu.; Shundrina, Inna K.; Kazantsev, Maxim S.
Abstract : Combination of Suzuki cross-coupling and McMurrey reactions yielded materials with controllable molecular self-doping and luminescence. Abstract : Molecular doping of organic luminescent materials is an efficient tool to tune their optoelectronic properties. In particular, self-doping by luminescent longer-conjugation chain chemical by-products is a convenient way to obtain highly emissive organic semiconductors. Although the self-doping approach allows us to avoid the necessity of dopant synthesis, to realize the self-doping and optimize dopant concentration there is a need for a stepwise gradual purification of a material which may be problematic. Here we report a synthetic approach allowing us to control self-doping in luminescent organic semiconductors based on arylene-vinylene co-oligomers. We designed 1, 2-bis(5-(4-octylphenyl)thiophen-2-yl)ethene (C8-BPTE) and synthesized it via two pathways yielding batches with different self-dopant concentrations. Our approach does not require a complex purification and excludes a possible degradation of the materials under sublimation or chromatography conditions. The optical properties of C8-BPTE crystals have been demonstrated to be finely tuned by simple mixing of synthesized batches of the material in a desired proportion, the increase of self-doped material content showed an increase in PL QY by up to 1.7 times and caused a red shift of photoluminescence spectra. Moreover, C8-BPTE demonstrated good film-formation ability and the substrate-inclined crystallization showed an efficient way to control crystal lateral size and its orientation on the substrate. C8-BPTE thin-film also demonstrated good p-type charge transport in solution-processed organic field-effect transistors with mobility of up to 0.1 cm 2 V −1 s −1 .